MOBILE WEB-BASED DYNAMIC FILING MANAGEMENT INFORMATION SYSTEM DESIGN - Toni Wijanarko Adi Putra; Isaac Vital; Migunani (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Sub-districts according to the composition, position, duties are regulated by government decree. As a regional body, the Camat is given power. In addition, districts also carry out public administration tasks. North Semarang Village, having its address at Jl Taman Brotojoyo No. 02 Semarang, functions related to the management of outgoing letters and receipt of incoming letters are carried out by recording them in a ledger and securing each incoming and outgoing letter by the head of the personnel department and general sub-section and stored in the existing cupboard. This again brings problems when searching for old data, because it may not know where it is stored, it may be corrupted or it may be lost from memory. This method is ineffective and has many drawbacks. Storing incoming and outgoing mail in the mailbox, for example, can easily spoil mail as more and more letters accumulate each day. Not to mention the nature of the room that is wet and insects accelerate paper damage. On the other hand, documenting incoming and outgoing letters through an agenda book also lengthens the registration process. Under these conditions, it is necessary to develop a mobile web-based filing management information system.